2006 Florida Citrus Pest Management Guide: Soft-Bodied Insects Attacking Foliage and Fruit - Harold W. Browning; Carl C. Childers; Philip A. Stansly; Jorge Peña; Michael E. Rogers (EDIS)
Revised! ENY-604, an 8-page section of the Citrus Pest Management Guide by H.W. Browning, C.C. Childers, P.A. Stansly, J. Peña and M.E. Rogers, provides information on the group of insects belonging to the order Homoptera (scale insects, mealybugs, whiteflies, psyllids, and aphids), which affect foliage, twigs, and fruit of citrus in Florida. A section on the citrus leafminer, a moth species, is also included. Includes discussion of families and species, and tables of management options. This version expands the psyllids section to include a discussion of their role as a vector of Citrus Greening (Huanglongbing) Disease, and adds the IRAC Mode of action class for each pesticide listed in the tables. Published by the UF Department of Entomology and Nematology, October 2005.